DMAG, a novel countermeasure for the treatment of thrombocytopenia - Jing Lin (BMC, 2021)
Abstract Background Thrombocytopenia is one of the most common hematological disease that can be life-threatening caused by bleeding complications. However, the treatment options for thrombocytopenia remain limited. Methods In this study, giemsa staining, phalloidin staining, immunofluorescence and flow cytometry were used to identify the effects of 3,3ʹ-di-O-methylellagic acid 4ʹ-glucoside (DMAG), a natural ellagic acid derived from Sanguisorba officinalis L. (SOL) on megakaryocyte differentiation in HEL cells. Then, thrombocytopenia mice model was constructed by X-ray irradiation to evaluate the therapeutic action of DMAG on thrombocytopenia. Furthermore, the effects of DMAG on platelet function were evaluated by tail bleeding time, platelet aggregation and platelet adhesion assays. Next, network pharmacology approaches were carried out to identify the targets of DMAG. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were performed to elucidate the underling mechanism of DMAG against thrombocytopenia. Finally, molecular docking simulation, molecular dynamics simulation and western blot analysis were used to explore the relationship between DAMG with its targets. Results DMAG significantly promoted megakaryocyte differentiation of HEL cells. DMAG administration accelerated platelet recovery and megakaryopoiesis, shortened tail bleeding time, strengthened platelet aggregation and adhesion in thrombocytopenia mice. Network pharmacology revealed that ITGA2B, ITGB3, VWF, PLEK, TLR2, BCL2, BCL2L1 and TNF were the core targets of DMAG. GO and KEGG pathway enrichment analyses suggested that the core targets of DMAG were enriched in PI3K–Akt signaling pathway, hematopoietic cell lineage, ECM-receptor interaction and platelet activation. Molecular docking simulation and molecular dynamics simulation further indicated that ITGA2B, ITGB3, PLEK and TLR2 displayed strong binding ability with DMAG. Finally, western blot analysis evidenced that DMAG up-regulated the expression of ITGA2B, ITGB3, VWF, p-Akt and PLEK. Conclusion DMAG plays a critical role in promoting megakaryocytes differentiation and platelets production and might be a promising medicine for the treatment of thrombocytopenia. Graphical Abstract